If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -4x = 12x + 126 Reorder the terms: 23 + -4x = 126 + 12x Solving 23 + -4x = 126 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 23 + -4x + -12x = 126 + 12x + -12x Combine like terms: -4x + -12x = -16x 23 + -16x = 126 + 12x + -12x Combine like terms: 12x + -12x = 0 23 + -16x = 126 + 0 23 + -16x = 126 Add '-23' to each side of the equation. 23 + -23 + -16x = 126 + -23 Combine like terms: 23 + -23 = 0 0 + -16x = 126 + -23 -16x = 126 + -23 Combine like terms: 126 + -23 = 103 -16x = 103 Divide each side by '-16'. x = -6.4375 Simplifying x = -6.4375
| 15t=17+8-24 | | 4x+.80=25 | | 8k-5=51 | | 9w-26=28 | | 2x-4(x-5)=-6+5x-2 | | 5(10-4x)=290 | | 5(4)=16x | | 5t+4=36 | | 79=5u+14 | | -29(t+253)=406 | | -12/x=3-18/x-4 | | 5x+10=2+18 | | 3/6=13/x | | 79=u+14 | | 5x+10=2+15 | | 108=8y-3x | | -35=-5+5y | | n+(-9)=-9 | | 5x+10=2+20 | | (2+2y)+(3+5c)= | | 2(2x-3)-2x^2=(3-2x)x | | 1(x+15)=1x | | 5(x+3)=16y | | -11(k-862)=-803 | | 2u+11=51 | | 18p+36p=4884 | | 5x-1=19-4x | | 12x+8=18x-3 | | 5x-4+2(x+4)=16 | | 2(5x-y)=0 | | -(9-7a)-(10+6a)-9=-(7-5a)+(-a)+6 | | 18+0.05n=50.50 |